2015
DOI: 10.1002/bmb.20883
|View full text |Cite
|
Sign up to set email alerts
|

Views from academia and industry on skills needed for the modern research environment

Abstract: Reports from employers of higher education graduates indicate the existence of a considerable gap between the skills required by employers and those possessed by recent graduates. As a first step toward closing this gap, this study aims to determine its origin. Interviews with nine research-active biochemistry professionals were used to identify the most important skills for biochemistry students to succeed in research positions postgraduation. The results of these interviews were used to develop a survey, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Additionally, the curriculum also reinforces a variety of highly transferrable skills related to the process of science, including critical thinking, inquiry and analysis, quantitative reasoning, information literacy, and written communication. These have been identified as essential learning outcomes in an undergraduate biochemistry and molecular biology degree program and undergraduate general education and are essential for success in post‐graduate employment in the life sciences .…”
Section: Overview Of the Curriculummentioning
confidence: 99%
“…Additionally, the curriculum also reinforces a variety of highly transferrable skills related to the process of science, including critical thinking, inquiry and analysis, quantitative reasoning, information literacy, and written communication. These have been identified as essential learning outcomes in an undergraduate biochemistry and molecular biology degree program and undergraduate general education and are essential for success in post‐graduate employment in the life sciences .…”
Section: Overview Of the Curriculummentioning
confidence: 99%
“…However, increasing undergraduate student participation places a greater burden on faculty time and resources, ultimately leading to a small number of students in a given lab and increased competition for yearlong UREs . In addition, little change or development in the basic structure and curriculum related to undergraduate research has been reported in the past decade, especially in the biomedical research environment , despite the trend in technological advances and professional needs in the research arena. There is a need to increase the number of students participating an academic year URE and to develop the URE to better fit skill‐sets needed in a biomedical research environment and post‐graduate education.…”
Section: Introductionmentioning
confidence: 99%
“…Little research exists on what knowledge practicing biochemists rely upon in their work. Recent surveys of practicing biochemists have identified concepts central to biochemistry and the skills and knowledge found to be deficit in recent graduates (Rowland et al , 2011; Talgar and Goodey, 2015). Although the results of these studies indicate that many chemical concepts are important for biochemistry, no study has investigated the relevance of CI for practicing biochemists.…”
Section: Research Design and Resultsmentioning
confidence: 99%